Derivations and centroids of four-dimensional associative algebras - Abdulkareem, Abdulafeez Olalekan; Fiidow, Mohamed Abubakar Hagi Mohamed; Rakhimov, Isamiddin Sattarovich (Academic Publications, 2017)
In the paper derivations and centroids of four-dimensional associative algebras are described. We also identify the class of algebras called characteristically nilpotent among four-dimensional associative algebras.